Screen cleaner for on farm processing of grains - ARADWAD, PRAMOD P; T V, ARUN KUMAR; SINHA, J P; YADAV, RAHUL S (The Indian Journal of Agricultural Sciences, 2021)
Cleaning is the first unit operation performed on threshed grain to remove field impurities. Presently, cleaning machines are operated using conventional energy sources which are either uncertain or non-affordable to farmers. A solar powered multi-crop screen cleaner was developed (2014), modified and tested at ICAR-Indian Agricultural Research Institute, New Delhi (2016).The modified unit consists of the frame, feed hopper and discharge chutes, adjustable screen cradle assembly, slope adjustment mechanism for screen and screen cradle and a variable drive unit. Developed machine was tested for soybean, lentil and chickpea and evaluated in terms of cleaning efficiency at different feed rate, speed and screen slope. The optimum performance was achieved at a screen slope of 5°, 200 rpm, and feed rate of 150 kg/h. Cleaning efficiency in the range of 74-79 % was observed. Multi-grain processing ability, better cleaning efficiency and green energy utilisation assures that the developed machine is an appropriate techno-economic solution for on farm grain processing.